Evaluation of five commercial methods for the extraction and purification of DNA from human faecal samples for downstream molecular detection of the enteric protozoan parasites Cryptosporidium spp., Giardia duodenalis, and Entamoeba spp - Paulos, Silvia; Mateo, Marta; de Lucio, Aida; Hernández-de Mingo, Marta; Bailo, Begoña; Saugar, José M.; Cardona, Guillermo A.; Fuentes, Isabel; Mateo, María; Carmena, David (Journal of microbiological methods, 2016)
High quality, pure DNA is required for ensuring reliable and reproducible results in molecular diagnosis applications. A number of in-house and commercial methods are available for the extraction and purification of genomic DNA from faecal material, each one offering a specific combination of performance, cost-effectiveness, and easiness of use that should be conveniently evaluated in function of the pathogen of interest. In this comparative study the marketed kits QIAamp DNA stool mini (Qiagen), SpeedTools DNA extraction (Biotools), DNAExtract-VK (Vacunek), PowerFecal DNA isolation (MoBio), and Wizard magnetic DNA purification system (Promega Corporation) were assessed for their efficacy in obtaining DNA of the most relevant enteric protozoan parasites associated to gastrointestinal disease globally. A panel of 113 stool specimens of clinically confirmed patients with cryptosporidiosis (n=29), giardiasis (n=47) and amoebiasis by Entamoeba histolytica (n=3) or E. dispar (n=10) and apparently healthy subjects (n=24) were used for this purpose. Stool samples were aliquoted in five sub-samples and individually processed by each extraction method evaluated. Purified DNA samples were subsequently tested in PCR-based assays routinely used in our laboratory. The five compared methods yielded amplifiable amounts of DNA of the pathogens tested, although performance differences were observed among them depending on the parasite and the infection burden. Methods combining chemical, enzymatic and/or mechanical lysis procedures at temperatures of at least 56°C were proven more efficient for the release of DNA from Cryptosporidium oocysts. •The five purifications methods evaluated yielded amplifiable DNA of enteric protozoan parasites of public health relevance.•Performance differences were observed depending on the method assessed, the parasite considered, and the infection burden.•Combination of various lysis procedures at ≥56°C was more efficient for the release of Cryptosporidium DNA.•Performance, cost-effectiveness, and easiness of use should be considered when choosing a given DNA purification method.